2019
DOI: 10.1155/2019/8912390
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Structural Reliability of Steel Frames Using Posttensioned Connections

Abstract: In this paper, various moment-resisting steel frames (MRSFs) are subjected to 30 narrow-band motions scaled at different ground motion intensity levels in terms of spectral acceleration at first mode of vibration SaT1 in order to perform incremental dynamic analysis for peak and residual interstory drift demands. The results are used to compute the structural reliability of the steel frames by means of hazard curves for peak and residual drifts. It is observed that the structures exceed the threshold residual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In other words, it is observed that the values of the mean annual rates of exceedance for the RC-BRB systems are smaller than those of the traditional RC buildings. Note that there are other structural systems to improve the seismic reliability of buildings such as posttensioned connections [45]. e results indicate that the use of BRBs in buildings is a good solution in order to reduce peak drift demands of traditional structures located in high seismic zones.…”
Section: Structural Reliabilitymentioning
confidence: 95%
“…In other words, it is observed that the values of the mean annual rates of exceedance for the RC-BRB systems are smaller than those of the traditional RC buildings. Note that there are other structural systems to improve the seismic reliability of buildings such as posttensioned connections [45]. e results indicate that the use of BRBs in buildings is a good solution in order to reduce peak drift demands of traditional structures located in high seismic zones.…”
Section: Structural Reliabilitymentioning
confidence: 95%
“…The safeguard of the built heritage is gaining an increasing interest in structural and seismic engineering [1,2]. The knowledge of the seismic response of the structures plays a fundamental role in the evaluation of the seismic vulnerability of existing structures [3][4][5][6] and in the prediction of the expected losses [7][8][9]. The designer, to achieve a correct safety evaluation in terms of the capacity demand ratio, must resort to non−linear models and non−linear analyses [10][11][12][13], which, even though they are described in the codes, are very prone to being misinterpreted.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have investigated the behavior of connections [35][36][37][38][39]; also, the behavior of prefabricated beam-to-column connections were studied by many researchers [40][41][42] among which [40] utilized short post-tensioned prestressed strands to prevent on-site aerial tensions. Furthermore, the connection of H-Shaped steel beam to box columns with flange plate connection was scrutinized by [43].…”
Section: Introductionmentioning
confidence: 99%